H-OPE: Health Online Personalized Education / Naffisah Mohd Hassan … [et al.] - Mohd Hassan, Naffisah; Shahrom, Melissa; Kassim, Dr. Erne Suzila; Maon, Dr. Siti Noorsuriani (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Globally, an increase of 20% yearly in chronic disease such as diabetes is sending us a red alert. The prevalence of diabetes mellitus in Malaysia especially Type 2, has increased to epidemic proportions. According to the Second National Health and Morbidity survey it is estimated that 3.4 million Malaysians are diabetes sufferers in 2010. Early identification and management might reduce the incidence of diabetes and its related complications. This indicates that prevention strategies to curb the rising rates of this disease are urgently needed. Therefore, a self-diagnostic tool is seen as a complementing program to identify the symptom of diabetes. Using a tested and approved model a diagnostic tool is design to educate the society on potential risk of diabetes. Depending on the results of the self-diagnostics user will be directed to tailored information of healthy lifestyle for a better living.